Analysis of Active Learning Strategies in Learning the Qur’an and Hadith - siti aisyah; Andika; M. Fadli (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to analyze active learning strategies in learning the Qur'an and Hadith as an alternative to increase student participation and understanding. The formulation of the problem in this study includes three main things: (1) what is meant by active learning strategies, (2) how to apply them in learning the Qur'an and Hadith, and (3) what are the advantages and challenges faced in their implementation. The method used is qualitative research with the type of library research, using a descriptive-analytical approach. Data were collected through documentation studies of relevant literature and analyzed using content analysis techniques. The results of the discussion show that active learning strategies, such as group discussions, project-based learning, contextual case studies, and the use of digital media, can increase student involvement cognitively, affectively, and psychomotorically. This strategy also supports the internalization of Islamic values ??derived from the Qur'an and Hadith. However, its implementation faces various challenges, such as time constraints, lack of teacher readiness, and constraints on facilities and evaluation. With adequate planning and support, active learning strategies can be an effective and relevant approach in Al-Qur’an Al-Hadith education.